Meggs' history of graphic design - Meggs, Philip B.; Purvis, Alston W., 1943-; Meggs, Philip B. (Hoboken, N.J. : John Wiley & Sons, 2012)
"In addition to classic topics such as the invention of writing and alphabets, the origins of printing and typography, and postmodern design, the new Fifth Edition presents new information on current trends and technologies sweeping the graphic design landscape, such as the web, multimedia, interactive design, and private presses, ..."--Book jacket.
Part I. The prologue to graphic design : 1. The invention of writing -- 2. Alphabets -- 3. The Asian contribution -- 4. Illuminated manuscripts -- Part II. A graphic renaissance : 5. Printing comes to Europe -- 6. The German illustrated book -- 7. Renaissance graphic design -- 8. An epoch of typographic genius -- Part III. The bridge to the twentieth century : 9. Graphic design and the Industrial Revolution -- 10. The Arts and Crafts Movement and its heritage -- 11. Art Nouveau -- 12. The genesis of twentieth century design -- Part IV. The modernist era : 13. The influence of modern art -- 14. Pictorial modernism -- 15. A new language of form -- 16. The Bauhaus and the new typography -- The modern movement in America -- Part V. The age of information : 18. The international typographic style -- 19. The New York school -- 20. Corporate identity and visual systems -- 21. The conceptual image -- 22. Postmodern design -- National visions within a global dialogue -- 24. The digital revolution and beyond.
Rev. ed. of: A history of graphic design. c1998.
Includes bibliographical references (p. [574]-581) and index.
Keywords: Graphic design (Typography) -- History; Book design -- History